The love elixir of Augusta Stern : a novel [large type] - Loigman, Lynda Cohen (Thorndike Press large print historical fiction., 2025)
"As a teenager in the 1920s, Augusta's role model was her father, Solomon Stern, owner of the local pharmacy and the neighborhood expert on every ailment. But when Augusta's mother dies and Great Aunt Esther moves in, Augusta can't help but be drawn to Esther's unconventional remedies. As Augusta prepares for pharmacy college, she impulsively uses Esther's most potent elixir, with disastrous consequences. Sixty years later, Augusta is still haunted by the mistakes of the past. What happened all those years ago and how did her plan go so spectacularly wrong? And can Augusta reclaim the magic of her youth before it's too late?"-Back cover.